Trajetória do IFRN em inclusão escolar - Rodrigues, Maria Rita Vitor Martins (2010)
Discussions over the topic of inclusion of handicapped people at school are considered recent, but they have become more and more frequent within the national and international scenario. Such discussion has also being inserted in the speeches and actions of the school institution and with the formation of educators. This investigation is made necessary as a way to collect elements to reconsider the actions for the inclusion of the special education need youth. In special the visually handicapped ones, at Instituto Federal de Educação, Ciência e Tecnologia do Rio Grande do Norte (IFRN). The creation of a support unit functions as main vehicle for the actions of the institution. It is intended to know what young people with limitations have to say regarding their experiences as a way to signal paths to be and not to be followed by the support unit. Therefore, the experience which these young boys and girls have is of crucial importance. In order to accomplish the task, it was decided to use methodological elements based upon elements supported by the life reports of two deficient students here called Borges and Stéfano. Their reports are from childhood to their arrival at IFRN. From their reports, categories appeared: childhood and the role of family; school life and, finally, related to the actions of the support unit of IFRN, being divided in inclusive actions and obstacles. The first one takes a second look at the actions of the family within the learning-teaching process of these students. The second category presents the moment in which students started to receive formal education per se. The last category constitutes the cornerstone of the investigation, for it analyses the process of inclusion in the institution, according to the perception of the students with visual limitations. The results signaled the need for shared intervention between students with Special Education Needs and school professionals in the elaboration of the Educational Planning, which guarantees the defense of the rights to an efficient teaching practice and effective in the process of inclusion of these students